Synthesis of a novel fluorescent sensor bearing dansyl fluorophores for the highly selective detection of mercury (II) ions - Nantanit Wanichacheva (2018)
A new macromolecule possessing two dansyl moieties and based on 2-[4-(2-aminoethylthio)butylthio]ethanamine was prepared as a fluorescent sensor and its mercury sensing properties toward various transition metal, alkali, and alkali earth ions were investigated. The designed compound exhibited pronounced Hg2+-selective ON-OFF type fluorescence switching upon binding. The new compound provided highly selective sensing to Hg2+in acetonitrile-water solvent mixtures with a detection limit of 2.49 x 10-7M or 50 ppb. The molecular modeling results indicated that ions-recognition of the sensor originated from a self assembly process of the reagent and Hg2+to form a helical wrapping structure with the favorable electrostatic interactions of Hg2+coordinated with sulfur, oxygen, nitrogen atoms and aromatic moieties. © 2010 by the authors.